2021
DOI: 10.4103/ijo.ijo_1604_21
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 RNA in a conjunctival swab sample in real-time-polymerase chain reaction positive COVID-19 patients and its association with comorbidity and severity at a designated COVID-19 hospital in Central India

Abstract: Purpose: To evaluate the presence of SARS-CoV-2 RNA in the conjunctival swab sample of positive confirmed COVID-19 patients and to find out its association with comorbidity and severity of COVID-19 disease. Methods: We conducted an observational cross-sectional study at a dedicated tertiary COVID-19 hospital in central India for a period of 8 weeks from February 2021to March 2021. We included patients who tested positive for SARS-CoV-2 RNA through nasopharyngeal swab an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The ocular mucosal milieu has been identified as the most susceptible region that can be affected by transmissible microorganisms, including viral and bacterial pathogens such as herpes simplex virus-1, influenza, Zika, and Staphylococcus aureus [ 16 , 28 , 47 51 ]. Previous studies have shown the presence of SARS-CoV-2 RNA and proteins in various ocular tissues and fluids, including conjunctiva, limbus, tears, and aqueous humor, indicating that the eye could be a potential site of infection and transmission [ 21 , 25 , 38 ]. It is believed that SARS-CoV-2 can be disseminated through the ocular surface via nasolacrimal ducts, which connect the ocular surface with the respiratory tract, facilitate aqueous exchange, and provide shared lymphoid tissues between these sites [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ocular mucosal milieu has been identified as the most susceptible region that can be affected by transmissible microorganisms, including viral and bacterial pathogens such as herpes simplex virus-1, influenza, Zika, and Staphylococcus aureus [ 16 , 28 , 47 51 ]. Previous studies have shown the presence of SARS-CoV-2 RNA and proteins in various ocular tissues and fluids, including conjunctiva, limbus, tears, and aqueous humor, indicating that the eye could be a potential site of infection and transmission [ 21 , 25 , 38 ]. It is believed that SARS-CoV-2 can be disseminated through the ocular surface via nasolacrimal ducts, which connect the ocular surface with the respiratory tract, facilitate aqueous exchange, and provide shared lymphoid tissues between these sites [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of ocular manifestations among COVID-19 patients has been shown to be 11.03% [ 17 ] and even higher (42.8%) amongst juveniles [ 18 ]. Although many studies have demonstrated the expression of SARS-CoV-2 binding receptors, angiotensin-converting enzyme 2 (ACE2) and a transmembrane serine protease, TMPRSS2, on ocular surfaces [ 19 , 20 ] and the presence of viral RNA in conjunctival swabs [ 21 , 22 ], tears [ 23 , 24 ], and aqueous humor [ 25 ], the possible ocular transmission, tropism, pathology, and long-term effect of COVID-19 on eye remains inconclusive. Moreover, patients with comorbidities such as diabetes have demonstrated increased SARS-CoV-2 morbidity and severity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 56 ] Furthermore, several studies showed the existence of SARS-CoV2 in the conjunctival discharges and tears, which are potential ways for spreading the virus into the nasopharynx or eye contact. [ 2 57 58 59 60 61 62 63 64 65 ] However, according to a recent systemic review, no-cut clinical evidence demonstrated that eyes are a transmission pathway for COVID-19. [ 2 ] Furthermore, the conjunctival sac is not a favorable place for SARS-CoV2 replication according to the findings of the conjunctival swabs of postmortem and alive patients.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 prevalence in tears has already been explored in other studies, ranging from 0% to 57% [ 27 , 28 ]. Most of these studies used only CS for tear collection [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], one study used only SS [ 43 ], and four other studies used both tear collecting methods [ 44 , 45 , 46 , 47 ]. Our study confirms previous findings that CS samples had a higher SARS-CoV-2 detection rate compared to SS samples, and the viral loads in tear samples were lower compared to nasopharyngeal samples [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%